A Prospective Randomized Study of Erector Spinae Plane Block Combined with General Anaesthesia Versus General Anaesthesia in Lumbar Spine Surgery - Vikram Reddy. V; Rama Krishna. S; Dr. Prudhvi. G; Lakshmi Pushpa. S (Academia Anesthesiologica International, 2022)
Background: By causing total muscular relaxation, preserving stable intraoperative hemodynamics, and offering prolonged analgesia in the immediate aftermath of surgery, they produce close to perfect operating conditions. [4] We anticipated that ESP block can be utilised well as a lumbar surgery analgesic since LA broadly extends cranially and caudally when conducted. Aim: To determine the superiority of ESP block as a mode of postoperative analgesia compared to multimodal analgesia in lumbar spine surgeries. Subjects and Methods: A prospective, randomized, comparative study. Study area: Department of Anaesthesia, at YASHODA HOSPITAL, Malakpet branch, Hyderabad, Telangana. Study Period: 1 year. Study population: ASA physical grade I, II, patients, satisfying the inclusion criteria, undergoing lumbar spine surgeries were included. Sample size: 60 patients were divided into two groups of 30 each. All the patients have undergone thorough pre anaesthetic evaluation on the day prior to surgery. Investigations were done depending on the age & associated co-morbidities. All system were examined including airway and surface anatomy where the block was given and the procedure to be carried out was explained to the patients. Patients were reassured to alleviate their anxieties. All the patients were kept nil per oral as per the fasting guidelines. Written informed consent was taken. Results: Total dose of analgesic required in first 24 hours in ESP group is 41.67 58.844, without ESP group 105 80.247 with p value 0.001 which is clinically significant. Mean duration for which the block acted effectively was 983.50 89.019 mins. It is taken from time of block given. Occurrence of nausea in ESP block was 4 out of 30(13.33%), without ESP block 5 out 0f 30(16.67%), with p value 0.718 which is clinically insignificant. Conclusion: Based on the results, we conclude that ESP block decreases the post-operative pain scores and opioid requirements and can be used as excellent component of multimodal analgesia, which is safe and easily performed with no major complications.